DETERMINAN NIAT BERWAKAF UANG MELALUI PLATFORM TOKOPEDIA DENGAN SIKAP SEBAGAI VARIABEL INTERVENING (Studi Pada Generasi Z Di Provinsi Banten) - Seli Rosmawati; Mohamad Ainun Najib; Nurul Fadhilah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study was to analyze the influence of perceived usefulness, perceived ease of use, subjective norms, and perceived risk on the intention to make cash waqf through Tokopedia, with attitude as an intervening variable among Generation Z in Banten Province. This study used a quantitative approach with primary data obtained through questionnaires distributed to 120 respondents selected using a purposive sampling technique. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 3 software. The results showed that perceived usefulness, perceived ease of use, and subjective norms had a positive and significant effect on the attitude and intention to make cash waqf through Tokopedia. Meanwhile, perceived risk had a negative effect on intention. Attitude was also proven to significantly mediate the relationship between the independent variables and the intention to make cash waqf. This study indicates that digital waqf platforms such as Tokopedia have significant potential to increase Generation Z's participation in cash waqf. Therefore, increasing digital literacy, public trust, and easy access to digital waqf services are crucial for optimizing cash waqf collection in Indonesia.